Model Pembelajaran Inkuiri Yurisprudensi untuk Mengembangkan Kemampuan Berpikir Kritis Siswa SD pada Pelajaran Pendidikan Agama Kristen [Jurisprudence Inquiry Learning Model to Develop Critical Thinking Skills of Elementary Students in Christian Religious Education Lessons] - Tumilantouw, Kireina Gabriela; Lindawati, Lindawati (Diligentia: Journal of Theology and Christian Education, 2025)
Christian education views critical thinking skills as an important aspect because, through critical thinking skills, students are encouraged to differentiate between correct and incorrect information. Critical thinking skills can also guide students to correct knowledge and be able to prove these truths in the classroom. Critical thinking skills in Indonesia are still very low. This is proven by the low PISA results achieved by Indonesia in 2018. Therefore, one way to develop critical thinking skills is to apply the Jurisprudential Inquiry learning model. The Jurisprudential Inquiry learning model can encourage students' critical thinking skills because students are continuously involved in learning to analyze and solve problems. This learning model can also stimulate students' curiosity about something so that students will take the initiative to look for facts and data related to the problem being discussed. This learning model is still relatively new and has been implemented in several middle and upper secondary schools. However, it is still not widely implemented, especially at the elementary school level because it is relatively new. This research aims to examine the importance of the Inquiry Learning Model in developing elementary students' critical thinking skills. The author uses a qualitative descriptive research method